x = 200 is NOT a solution to the equation x ÷ 2 - 40 = 10

z = 20 is NOT a solution to the equation 5 × (z - 6) = 30

z = 20 is NOT a solution to the equation 5 × (z - 6) = 30

Quoted By: >>10024031 >>10024046

>>10023971

This problem illustrates grouping like terms and dealing with subtraction in an equation.

Solve x - 12 + 20 = 37.

Replacing the -12 with a +(-12), we get

x + (-12) + 20 = 37.

Since addition is associative, the two like terms (the integers) may be combined.

(12) + 20 = 8

The left side of the equation becomes

This problem illustrates grouping like terms and dealing with subtraction in an equation.

Solve x - 12 + 20 = 37.

Replacing the -12 with a +(-12), we get

x + (-12) + 20 = 37.

Since addition is associative, the two like terms (the integers) may be combined.

(12) + 20 = 8

The left side of the equation becomes

Quoted By: >>10024049

Quoted By:

>>10024000

American Math, lulz. No wonder China and India are getting stronger a tech countries.

American Math, lulz. No wonder China and India are getting stronger a tech countries.

Quoted By: >>10024059

>>10024031

>>10024031

The x is multiplied by 2, therefore we divide both sides by 2 to solve for x:

2 × (5 + 1 + 4) = 20 ==>

2 × 10 = 20 ==>

20 = 20 so our solution is correct.

>>10024031

The x is multiplied by 2, therefore we divide both sides by 2 to solve for x:

2 × (5 + 1 + 4) = 20 ==>

2 × 10 = 20 ==>

20 = 20 so our solution is correct.

Quoted By: >>10024106

Quoted By: >>10024132

Quoted By:

Quoted By: >>10024187

Quoted By:

Quoted By:

Quoted By:

Quoted By: >>10024508 >>10024523

Are we back in elementary school math class? What the hell is this?

Quoted By:

Quoted By: >>10024644 >>10024728 >>10024816

>>10024508

3x + 6y = -6

Divide this equation by 3 and rearrange for x, then use this x in your other equation. You will be able to get a value for y. Then you can finally use this value to get a value for x.

3x + 6y = -6

Divide this equation by 3 and rearrange for x, then use this x in your other equation. You will be able to get a value for y. Then you can finally use this value to get a value for x.

Quoted By:

Quoted By:

Quoted By: >>10024777 >>10024787 >>10024812

solve for f'''(x) = 3x(sin(sin(sinx)))/2x(cos(sin(tanx)))

Quoted By:

>>10024734

Yami actually got it right. Except his post didn't end in 5. So much for King of GETs.

Yami actually got it right. Except his post didn't end in 5. So much for King of GETs.

Quoted By: >>10024804

Quoted By: >>10024822

Quoted By: >>10024821